PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, FREE CASH FLOW, SALES GROWTH, INVESTMENT OPPORTUNITY SET TERHADAP NILAI PERUSAHAAN DENGAN VARIABEL INTERVENING KEBIJAKAN HUTANG - Bhakti Helvi Rambe (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2014)
Profitability Analysis, Company Size, Free Cash Flow, Growth Sales, Investment Opportunity Set On Company Value With Intervening Variables Of Debt Policy This research uses causal method. The population is 143 companies, and 45 of them are used as samples, taken using purposive sampling techniques, so that there will be 179 units of observation. Data were analyzed using multiple linear regression analysis and path analysis. The results showed that, simultaneously, profitability, company size, free cash flow (FCF), sales growth, and investment opportunity set (IOS) had a significant effect on firm value. Partially, the variable Profitability and Firm Size has a positive and significant effect on firm value, Free Cash Flow (FCF), Sales Growth, and Investment Opportunities (IOS) have a positive but not significant effect on firm value. Debt to Equity Ratio (DER) has a negative influence on firm value. Simultaneously, Profitability, Firm Size, Free Cash Flow (FCF), Sales Growth, and Investment Opportunity Set (IOS) Investment Opportunity Set (IOS) Partially, the Profitability variable and Firm Size Size have a positive and significant influence on Free Cash Flow ( FCF), Sales Growth has a positive but not significant effect on Debt to Equity Ratio (DER). Meanwhile, Investment Opportunity Set (IOS) has a negative influence on Debt to Equity Ratio (DER), while Debt to Equity Ratio (DER) cannot mediate Profitability correlations, Company Size, Free Cash Flow (FCF), Sales Growth, and Sets Investment Opportunities (IOS) with Company Value.. Keywords: Profitability, Firm Size, Free Cash Flow, Sales Growth, Investment Opportunity Set, Firm Value, Debt to Equity Ratio